The Effect of Oregon Circuit Training and Fartlek Training on the VO2Max Level of Soedirman Expedition VII Athletes - Rifqi Festiawan; Andri Tria Raharja; Jeane Betty Kurnia Jusuf; Nanda Alfian Mahardika (Universitas Pendidikan Indonesia, 2020)
The research was aimed at determining the influence of Oregon Circuit Training and Fartlek Exercises on the VO2max level of the Soedirman Expedition VII athletes. The research method used was pre-experimental method with two group pre-tests post-test design. The population were 20 people. The total sampling technique was administered to obtain 20 samples. The research instrument used Multi Stage Fitness Test. This study was conducted from June 2019 to October 2019. The data analysis process was conducted by using T-Test. Results showed that there are influences of both types of exercises on the increase of Vo2Max, but there is no significant influence difference between the two. In other words, the more often the exercise is done, the better the Vo2Max level of the athletes. AbstrakPenelitian ini bertujuan untuk mengetahui pengaruh Oregon Circuit Training dan Latihan Fartlek terhadap tingkat VO2max pada atlet Soedirman Expedition VII. Metode penelitian menggunakan pre-experimental dengan two group pretest posttest design. Populasi berjumlah 20 orang dan menggunakan teknik total sampling sehingga diperoleh 20 sampel. Instrumen Penelitian menggunakan Instrumen Multi Stage Fitness Test. Penelitian ini dilaksanakan pada Juni 2019 sampai dengan Oktober 2019. Teknik analisis data diperoleh dengan Uji T. Hasil penelitian menunjukkan bahwa terdapat pengaruh dari kedua jenis latihan terhadap peningkatan Vo2Max namun tidak ada perbedaan pengaruh yang signifikan diantara keduanya. Dengan kata lain, semakin sering latihan dilakukan maka semakin baik tingkat Vo2Max Atlet.